KARAKTERISTIK KIMIA, FISIKA DAN SENSORIS PEMPEK LENJER KERING DENGAN KONSENTRASI CaCl2 - Saparudin, Arman; Murtado, A.D. (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2017)
This study aims to determine the effect of various concentrations of CaCl2 determine the characteristics of the chemical, physical and sensory pempek lenjer dry, knowing the role of CaCl2 treatment in the absorption of water and find out on how the use of CaCl2 concentration that produces pempek lenjer dry. This research was conducted in the laboratory of the Factulty of Agriculture, University of Muhammadiyah Palembang in April 2016 Until August 2016. This is study uses a randomized block design (RAK) are arranged in a fakorial with various concentrations of CaCl2 treatment factors in the manufacture of dry lenjer pempek consisting of six factors and the treatment was repeated four times. The parameters observed in this study is an analysis of the chemical include moisture and protein content, the analysis of physics include the degree of elasticity, water absorption pempek lenjer raw speed of water absorption pempek lenjer dry, long cooking time and volume development pempek lenjer dry and analysis of sensorilal attributes include aroma, color and flavor lenjer pempek dry. Treatment of various concentrations of CaCl2 very significant effect on the chemical charateristics (moisture and protein content), physics (the level of resilience, water absorption pempek lenjer raw speed of water absorption pempek lenjer dry, long cooking time and volume development pempek lenjer dry) and effect significant effect on sensory properties (aroma, colour and falvor) lenjer pempek dry. A level of the highest value to the aroma, colour and falvor pempek lenjer contained in C3 treatment with average values of 3.75, 3.90 and 3.95 are included criteria rather. Preffered Organoleptic test for aroma, colour and falvor Treatment C3 (CaCl2 concentration of 1.5% by weight of water immersion) have the highest preference level value than the treatment of C1, C2, C3, C4, C5 and C6 to get a good dry lenjer pempek authors suggest treatment should use C3 (CaCl2 concentration of 1.5% by weight of water immer.